Impacts of Skeletal Anterior Open Bite Malocclusion on Speech. Issue 2 (June 2022) - Keyser, Mary Morgan Bitler; Lathrop, Hillary; Jhingree, Samantha; Giduz, Natalie; Bocklage, Clare; Couldwell, Sandrine; Oliver, Steven; Moss, Kevin; Frazier-Bowers, Sylvia; Phillips, Ceib; Turvey, Timothy; Blakey, George; et al.
Introduction: Articulation problems are seen in 80% to 90% of dentofacial deformity (DFD) subjects compared with 5% of the general population, impacting communication and quality of life, but the causal link is unclear. We hypothesize there are both qualitative (perceptual) and quantitative (spectral) differences in properties of stop (/t/ or /k/), fricative (/s/ or /ʃ/), and affricate (/tʃ/) consonant sounds and that severity of anterior open bite (AOB) jaw disharmonies correlates with degree of speech abnormality.Methods: To test our hypotheses, surgical orthodontic records and audio recordings were collected from DFD patients (n = 39 AOB, 62 controls). A speech pathologist evaluated subjects, and recordings were analyzed using spectral moment analysis (SMA) to measure sound frequency distortions.Results: Perceptually, there is a higher prevalence of auditory and visual speech distortions in AOB DFD patients when compared to controls. Quantitatively, a significant ( P < .01) increase in the centroid frequency (M1) was seen in the /k/, /t/, /tʃ/, and /s/ sounds of AOB subjects compared to the controls. Using linear regression, correlations between AOB skeletal severity and spectral distortion were found for /k/ and /t/ sounds.Conclusions: A higher prevalence of qualitative distortions and significant quantitative spectral distortions in consonant sounds were seen in AOB patients compared to controls. Additionally, severity of skeletal AOB is correlated with degree of distortion for consonant sounds. These findings provide insight into how the surgical and/or orthodontic treatment of AOB may impact speech.